The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1111/j.1574-6941.2007.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity and light on organic carbon and nitrogen uptake in a hypersaline microbial mat

Abstract: Utilization of dissolved organic matter (DOM) is thought to be the purview of heterotrophic microorganisms, but photoautotrophs can take up dissolved organic nitrogen (DON) and dissolved organic carbon (DOC). This study investigated DOC and DON uptake in a laminated cyanobacterial mat community from hypersaline Salt Pond (San Salvador, Bahamas). The total community uptake of (3)H-labeled substrates was measured in the light and in the dark and under conditions of high and low salinity. Salinity was the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“…Despite this limitation, the prevalence of diazotrophic Rhizobiales and Rhodobacteriales in the artificial microbialites is consistent with previous analyses of nitrogen fixation in Bahamian stromatolites (53) and in Hamelin Pool of Shark Bay, Australia (42). Previous research has shown that noncyanobacterial nitrogen fixation may be important in mats whose cyanobacterial population tends to contain mostly nonheterocystous cyanobacteria (37,46,60,61), such as cyanobacteria with the sequences recovered in the Highborne Cay stromatolites.…”
Section: Discussionsupporting
confidence: 74%
“…Despite this limitation, the prevalence of diazotrophic Rhizobiales and Rhodobacteriales in the artificial microbialites is consistent with previous analyses of nitrogen fixation in Bahamian stromatolites (53) and in Hamelin Pool of Shark Bay, Australia (42). Previous research has shown that noncyanobacterial nitrogen fixation may be important in mats whose cyanobacterial population tends to contain mostly nonheterocystous cyanobacteria (37,46,60,61), such as cyanobacteria with the sequences recovered in the Highborne Cay stromatolites.…”
Section: Discussionsupporting
confidence: 74%
“…Competition theory presents an alternative mechanism to explain the increase in diversity with mat depth. We speculate that the pool of nutrients available for assimilation (primarily N and P ) may be limiting to heterotrophs in the oxic layer due to the large biomass of primary producers such as heterocystous Cyanobacteria and diatoms (Herbert and Welsh, 1994; Camacho and de Wit, 2003; Jonkers et al, 2003; Yannarell and Paerl, 2007). If competition for limiting nutrients, rather than competition for sources of C and energy, are resulting in competitive exclusion then we might expect competitive exclusion should not be as dominant a force deeper in the mat, allowing more taxa to coexist (Hutchinson, 1961).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that light availability can have a strong impact on the composition of cyanobacterial communities (Havens et al ., 1998). As photosynthetic mat communities experience increases in light availability previous studies have shown there is an increase in uptake of dissolved organic carbon (Yannarell and Paerl, 2007). The rate of uptake is influenced by the type and composition of the cyanobacterial communities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of uptake is influenced by the type and composition of the cyanobacterial communities (e.g. filamentous, colony coccoid or solitary coccoid; Yannarell and Paerl, 2007). The transition to the coccoid rich communities of the beige (enriched in colony‐forming Pleurocapsales ) or the pink (enriched in solitary Chroococcales ) mats may reflect seasonal differences in uptake or differences in the substrate‐utilization patterns of the two distinct mat types.…”
Section: Discussionmentioning
confidence: 99%